Research of nanomodified portland cement compositions with high early age strength - Marushchak, Uliana; Sanytsky, Myroslav; Mazurak, Taras; Olevych, Yuriy (Eastern-European Journal of Enterprise Technologies, 2016)
An innovative method for the creation of rapid hardening building composites with multifunctional purposes and specified properties under different operating conditions is their nanomodification. This technique is based on the principles of directional control and control over the processes of structure formation of material, as well as over kinetics and mechanism for chemical interactions at the early stages of the hardening process of cement matrix. Comprehensive assessment of particle size distribution of ultrafine mineral additives by the indicator of differential coefficient of surface activity was carried out. Physical and mechanical properties of the nanomodified Portland cement composition, which contain ultrafine mineral additives, polycarboxylate superplasticizer, alkaline containing accelerator of hardening, as well as nanoscale particles of calcium hydrosilicate, were investigated. Peculiarities of the phase composition and microstructure of nanomodified Portland cement composition were established by physical and chemical analysis methods. It was established that the examined Portland cement compositions are characterized by intensive development of early strength, and by the indicator of standard strength they are related to high strength binder. It is demonstrated that acceleration of the hardening processes of nanomodified Portland cement compositions is due to the optimization of particles packing of the system, the presence of energy-active particles in the composition of mineral additive, increasing of liquid phase alkalinity, stimulating of nucleation processes in the inter-grain space due to heterogeneous or homogeneous nucleation, accelerating of reactions associated with pozzolanic activity of ultrafine additives. A widespread using of rapid hardening concretes based on the nanomodified Portland cement compositions with high strength at an early age will provide for an increase in efficiency of erecting monolithic structures, road infrastructure objects, of manufacturing precast reinforced concrete products, of carrying out repair and restoration works, including those under different temperature conditions.